Participatory Action Research for Developing a Wellness-Promoting Model for Community-Dwelling Older Adults in Thailand - Jitdorn, Jurawan; Somprasert, Chomchuen; Hickman Jr., Ronald (The Journal of Behavioral Science, 2024)
Older adults have a high prevalence of long-term negative health consequences and this is a challenging public health concern. Aging brings an increase in the prevalence of chronic diseases, such as hypertension, diabetes, and dementia. Older adults face more challenges with everyday living activities. Promoting wellness for them is an important issue. This research study had two phases, phase I for examining the experiences, backgrounds, and health perspectives of older adults. In phase II, a participatory action research (PAR) approach was utilized for developing a wellness-promoting model for community-dwelling older adults in Thailand. A total of forty-six participants participated in interviews and focus groups. The results of phase I revealed seven factors related to the wellness behaviors of older adults: 1) physical, 2) psychological, 3) social, 4) family, 5) age-friendly environment, 6) life goals, and 7) spiritual. These findings were used for creating the preliminary wellness-promoting model in phase II, which consisted of four input factors, namely, personal, family, social, and environmental factors. All these factors affected the cycle of change among older adults. This cycle consisted of three steps. The first was to promote self-competence, the second was to promote self-empowering, and the last was to promote growth. The output of the model was aging independently with four components: 1) physical fitness, 2) psychological fitness, 3) spiritual fitness, and 4) social fitness. This model can be applied continuously and sustainably because it suits older individuals’ lifestyles, cultures, and community contexts.